Mazhab Filsafat Hukum Islam: Urgensi Pengajaran Di Perguruan Tinggi Di Indonesia - Saepul Rochman; Kelik Wardiono; Arief Budiono (Jurnal Hukum Replik, 2021)
This study aims to compare the teaching of the philosophy of law in Universities in Indonesia. The approach used in this article is a comparative study. The results of this study indicate that in general the teaching of legal philosophy in Indonesia is dominated by the content of the European-Western legal philosophy. This study also finds that the schools of Islamic legal philosophy comprehensively discuss aspects of ontology, epistemology, legal sources and methodologies, and legal axiology through various themes that are also studied by Western European legal philosophy without separating but placing them in certain parts. In this regard, it is necessary to add a school of Islamic legal philosophy as part of the disciplines taught by law faculties in Indonesia, especially to treat equally between the Faculty of Islamic Law and the Faculty of Western Philosophy of Law, moreover, Islamic Law is part of the Indonesian legal system.Keywords: Law, School, Teaching, University, Philosophy